Collagen immobilization on ultra-thin nanofiber membrane to promote in vitro endothelial monolayer formation. (November 2019) - Park, Byeong-ung; Park, Sang Min; Lee, Kyoung-pil; Lee, Seong Jin; Nam, Yu Eun; Park, Han Sang; Eom, Seongsu; Lim, Jeong Ok; Kim, Dong Sung; Kim, Hong Kyun
The endothelialization on the poly (ε-caprolactone) nanofiber has been limited due to its low hydrophilicity. The aim of this study was to immobilize collagen on an ultra-thin poly (ε-caprolactone) nanofiber membrane without altering the nanofiber structure and maintaining the endothelial cell homeostasis on it. We immobilized collagen on the poly (ε-caprolactone) nanofiber using hydrolysis by NaOH treatment and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/sulfo- N -hydroxysulfosuccinimide reaction as a cost-effective and stable approach. NaOH was first applied to render the poly (ε-caprolactone) nanofiber hydrophilic. Subsequently, collagen was immobilized on the surface of the poly (ε-caprolactone) nanofibers using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/sulfo- N -hydroxysulfosuccinimide. Scanning electron microscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, and fluorescence microscopy were used to verify stable collagen immobilization on the surface of the poly (ε-caprolactone) nanofibers and the maintenance of the original structure of poly (ε-caprolactone) nanofibers. Furthermore, human endothelial cells were cultured on the collagen-immobilized poly (ε-caprolactone) nanofiber membrane and expressed tight junction proteins with the increase in transendothelial electrical resistance, which demonstrated the maintenance of the endothelial cell homeostasis on the collagen-immobilized-poly (ε-caprolactone) nanofiber membrane. Thus, we expected that this process would be promising for maintaining cell homeostasis on the ultra-thin poly (ε-caprolactone) nanofiber scaffolds.